Konseling Tekhnik Menyusui pada Ibu Postpartum di RSUD Temanggung - Eva Desitasari; Yulianti, Rizkhiana; Hapsari Windayanti; Tristiana (Universitas Ngudi Waluyo, 2025)
One of the most enjoyable moments after birth is the process of breastfeeding a baby. When breastfeeding a baby is a moment to establish closeness between mother and baby and rarely in this breastfeeding process there are several complaints from the mother, including breast milk that does not come out, the baby cannot breastfeed, and sore nipples. Based on data from the Basic Health Research (Riskesdas) in 2010, it was explained that 67.5% of mothers who failed to provide exclusive breastfeeding to their babies were due to the mother's lack of understanding of the correct breastfeeding technique, so that they often experience sore or cracked nipples. This community service activity is a form of effort to increase knowledge and skills about the correct breastfeeding technique. It is expected that postpartum mothers provide breast milk with the correct technique so that they can provide exclusive breastfeeding for at least 6 months. The number of postpartum mothers participating was 20 people. The method of implementing Community Service activities is carried out in 3 stages, namely: the planning stage, the implementation stage of community service activities and the evaluation stage. The results of mothers' knowledge about the correct breastfeeding technique before being given counseling were conducted pretest, most had good knowledge as many as 4 (15%), sufficient as many as 9 (55%) and lacking as many as 7 (30%). From the community service carried out after being given counseling about the correct breastfeeding technique and conducted posttest all respondents had good knowledge as many as 20 (100%). This shows the success of community service activities, mothers' knowledge after being given counseling about the correct breastfeeding technique to overcome problems during breastfeeding in postpartum mothers. Abstrak Salah satu yang paling menyenangkan pada saat setelah kelahiran adalah proses menyusui bayi. Pada saat menyusui bayi merupakan moment untuk menjalin kedekatan ibu dan bayi dan jarang dalam proses menyusui ini muncul beberapa keluhan dari ibu, antara lain ASI yang tidak keluar, bayi yang tidak bisa menyusui, putingnya lecet. Berdasarkan data dari Riset Kesehatan Dasar (Riskesdas) tahun 2010 dijelaskan bahwa 67,5% ibu yang gagal memberikan ASI ekslusif kepada bayinya adalah kurangnya pemahaman ibu tentang teknik menyusui yang benar, sehingga sering mengalami puting lecet ataupun retak. Kegiatan pengabdian masyarakat ini sebagai bentuk upaya untuk meningkatkan pengetahuan dan keterampilan tentang teknik menyusui yang benar. Diharapkan ibu postpartum memberikan ASI dengan teknik yang benar sehingga memberikan ASI eksklusif minimal 6 bulan. Jumlah peserta ibu nifas yaitu berjumlah 20 orang. Metode pelaksanaan kegiatan Pengabdian Masyarakat dilakukan dengan 3 tahap yaitu: tahap perencanaan, tahap pelaksanaan kegiatan pengabdian masyarakat dan tahap evaluasi. Hasil dari pengetahuan ibu tentang tekhnik menyusui yang benar sebelum diberikan penyuluhan dilakukan pretest sebagian besar berpengetahuan baik sebanyak 4 (15%) , cukup sebanyak 9 (55%) dan kurang sebanyak 7 (30%). Dari pengabdian masyarakat yang dilakukan setelah diberikan penyuluhan tentang tekhnik menyusui yang benar dan dilakukan posttest seluruh responden memiliki pengetahuan baik sebanyak 20 (100%). Hal ini menunjukkan keberhasilan dalam kegiatan pengabdian Masyarakat, pengetahuan ibu setelah diberikan penyuluhan tentang tekhnik menyusui yang benar untuk mengatasi permasalahan selama menyusui pada ibu postpurtum.